Historicko‑demografické bádanie na Slovensku - Pavol Tišliar (Historica, 2022)
The paper deals with an overview of historical‑demographic research in Slovakia. It names selected important works that contributed to the enlihtenment of the population history of Slovakia and personalities who directly addressed this issue. The paper pays particular attention to the institutionalization of historical‑demographic research in Slovakia and workplaces. There, the paper focuses on demographic research, especially in terms of the projecting and publishing area.